A Soft Robotic Textile‐Actuated Anthropomorphic Artificial Shoulder Mechanism - Bibhu Sharma; James Davies; Emanuele Nicotra; Adrienne Ji; Kefan Zhu; Phuoc Thien Phan; Chi Cong Nguyen; Trung Thien Hoang; Jingjing Wan; Patrick Pruscino; Hoang‐Phuong Phan; Nigel H. Lovell; et al. (Advanced Intelligent Systems)
Replicating the human shoulder in anthropomorphic systems is notoriously challenging due to its complex combination of mobility and strength. This study presents the design, fabrication, and control of a new soft artificial shoulder that achieves a broad range of motion, torque, and compliance. Powered by soft robotic textiles consisting of a network of hydraulic artificial muscles, the engineered shoulder effectively mimics intricate shoulder movements, including flexion/extension, abduction/adduction, and medial/lateral rotation. Experiments demonstrate that the artificial shoulder can generate a peak torque of 9.6 ± 0.1 Nm, covering 65.3% of the human shoulder workspace. The artificial shoulder capability is demonstrated through several experimental testbeds. First, it is employed to develop a gesture‐controlled telemanipulation robotic system, applicable to robot‐assisted surgery, hazardous environment operations, gaming, and rehabilitation. Second, it serves as a platform for simulating and studying neurological disorders, such as Parkinson's disease. This approach offers a reliable in vitro testing ground for wearable device validation, providing a crucial intermediary step before progressing to user studies. The artificial shoulder marks a significant advancement in next‐generation anthropomorphic systems, closely mimicking the human musculoskeletal system, with promising applications in wearable assistive devices, haptics, orthopedic testing, and medical technologies.